Effect of Soybean Meal from Different Midwest Soybean Varieties on Growth Performance of Broilers - Kara M. Dunmire; Michaela B. Braun; Caitlin E. Evans; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
At hatch, 360 one-d old Cobb500 male broilers were placed in battery cages to determine the effect of soybean meal (SBM) from different Midwest soybean varieties on growth performance of broilers. There were 6 broilers per cage and 15 replicates per treatment. Dietary treatments cons0isted of 1 of 4 soybean sources varying in quality determined by crude protein (CP) content and processed into SBM. Two sources consisted of soybeans from a similar region and processed either commercially solvent extracted or experimentally solvent extracted at Texas A&M University. Additional sources included a low quality and high quality soybean, experimentally solvent extracted into SBM at Texas A&M University. Therefore, dietary treatments consisted of a commercially processed SBM with 47% CP (CSBM), or experimentally processed SBM with 42% CP (42SBM), 49% CP (49SBM), or 52% CP (52SBM). Diets were formulated to 1.05% digestible Lys and balanced using digestible AA values previously determined. Added dietary fat provided by vegetable oil was kept constant in the formulation across treatments. Data were analyzed using the GLIMMIX procedure in SAS 9.4, with cage as the experimental unit, cage location as the blocking factor with Tukey-Kramer adjustment for multiple comparisons used. From d 0 to 18, body weight gain (BWG) and d 18 BW increased (P<0.001) in broilers fed CSBM, compared to 42SBM, 49SBM, and 52SBM. Broilers fed the CSBM had increased (P<0.001) ADFI, compared to 42SBM and 52SBM, with 49SBM intermediate. There was no evidence for feed conversion ratio (FCR) differences in broilers fed 42SBM, 49SBM, and 52SBM. There was no evidence for difference among broilers fed experimentally processed soybean meal; however, there were increases in diet cost of 28.81 and 5.41 per ton for the 42SBM and 49SBM, respectively, compared to 52SBM. Feed cost per bird decreased (P<0.001) in birds fed 52SBM (0.244) compared to CSBM (0.271) and 42SBM (0.266) with 49SBM (0.256) intermediate, CSBM and 42SBM. Therefore, the lower inclusion of 52SBM in the diet could be used to maintain growth performance with potential cost savings.
Keywords: soybean meal quality; broiler growth performance; amino acids; poultry